Antiradical effect of low-molecular peptides in extracts and hydrolyzates from tissues of water organisms - Ekaterina P. Karaulova; Anna I. Chepkasova; Tatiana N. Slutskaya; Lidia V. Shulgina; Eugeny V. Yakush (Известия ТИНРО)
Molecular-weight composition of peptides in extracts and hydrolyzates from soft tissues of the clams Corbicula japonica and Mercenaria mercenaria and liver of chum salmon is investigated. Antiradical activity is defined for low-molecular peptides, as well as for high-molecular proteins and free amino acids in the extracts. The maximum activity is detected for the extracts of salmon liver; all protein fractions in the water extract of the liver have antiradical activity. Low-molecular peptides and free amino acids have antiradical activity in all samples. The peptides with molecular weight 4.3 kDa have the highest activity in the water extract from C. japonica (43 units) and the peptides with molecular weight 4.7 kDa - in the water extract from M. mercenaria (5.6 units). After hydrolysis, the portion of low-molecular peptides increases for C. japonica , M. mercenaria , and salmon liver in 22.1, 14.5, and 11.1 %, respectively. Hence antiradical activity for hydrolyzates from C. japonica and M. mercen aria is in 1.9 times higher and for hydrolyzates from salmon liver - in 1.3 times higher than for water extracts from their tissues. Only the peptides with molecular weight 2.8-4.7 kDa have antiradical activity in the hydrolyzates; its value is 1-24 activity units for M. mercenaria ; 13-76 units for C. japonica and about 40 units for the chum salmon liver. Correlation is found between the content of peptides with molecular weight 3-4 kDa in hydrolyzates and their antiradical activity.